Television as a media and its role in psychological warfare"" - جحجاح غزوان; يسرى زريقة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
In our current era, the media plays an essential and important role in the lives of individuals and societies, especially after the technological and technical development that the world has witnessed since the beginning of the twentieth century, starting from the invention of television to the Internet and technological development, and the resulting inventions and innovations such as the emergence of satellites that resulted in Many satellite channels, which began to spread with the end of the twentieth century. Western countries have employed the digital, technological and technical revolution, and the communications and information revolution and made the best use of it in various fields, especially in the field of media and its various means, which have invested in many fields, not only economic, political, social and cultural, but also in military operations as well. , such as the media coverage of the military forces, or its production of a set of media programs or documentaries for field war operations, or military media In addition to exploiting its capabilities and capabilities in the psychological and propaganda warfare that accompanies war battles and military operations, and therefore the media has become an integral part of war operations, and plays an essential role in psychological wars that may be practiced sometimes before, after, or accompanying military wars